PENERAPAN TEKNIK ADP DALAM BELAJAR MEMAINKAN TALEMPONG PACIK DI SMP NEGERI 1 PAINAN - Prassetyo Fajar Gumilang; Tulus Handra Kadir; Harisnal Hadi (SENDRATASIK UNP, 2018)
Abstract This research aimed to know the implementation and application of ADP technique in learning talempong pacik on arts and cultures subject in the second semester, class VIII.1 of SMP Negeri 1 Painan. This research was classified to applied research. Instrument in this study was the researcher itself assisted by stationery, camera and audio recorder. The techniques of data collection used were observation, interviews, document study and documentation. The results of this study showed that in applying ADP technique, the students were asked to present the play of Talempong Pacik during three meetings. The points assessed in that performance were presentation, harmony, and technique. After the implementation of ADP technique, the teacher got results from their score in that presentation, teachers found students who were less familiar and understood about playing talempong pacik, and about 80% of the students understood. ADP techniques really helped the learners to understand how to play talempong pacik  in short time, i.e. three meetings. Keywords: ADP Technique, Talempong Pacik